Nanofibrous Scaffolds Functionalized with Serine for Dentin Mineralization: A Characterization Study - Krishnan, Aruna; Raghu, Sandhya; Somasundaram, Jayalakshmi (Biomedical Sciences and Clinical Medicine, 2025)
Objective Dentin repair and regeneration pose significant challenges in restorative dentistry due to its hierarchical structure and susceptibility to demineralization. Traditional approaches often fail to restore the naturalarchitecture and functionality of dentin. The aim of this study was to develop and characterize a biomimetic polycaprolactone (PCL)/nanohydroxyapatite (nHA)/serine (Ser) scaffold to enhance dental mineralization and support tissue regeneration. The inclusion of serine, known for its ability to bind calcium and phosphate ions and guide hydroxyapatite crystal formation, could enhance nucleation and cell attachment, making the scaffold a promising biomaterial for dentin repair. Methods Nanofibrous scaffolds were fabricated using PCL, nHA, and Ser by the electrospinning method. The structural and functional properties of the scaffold were characterized through scanning electron microscopy (SEM), energy-dispersive x-ray spectroscopy (EDX), x-ray diffraction (XRD), and fourier transform infrared spectroscopy (FTIR). SEM and EDX were used to evaluate the morphology, porosity, and elemental composition. XRD analyzed the crystalline and amorphous phases, while FTIR analyzed chemical interactions among the components. Results SEM analysis revealed a uniform fibrous structure with interconnected porosity, mimicking the extracellular matrix. EDX confirmed the successful incorporation of calcium and phosphorus, indicating the presence of nHA. XRD analysis demonstrated a combination of crystalline and amorphous phases, highlighting the scaffold’s structural stability and bioactivity. FTIR spectroscopy identified characteristic peaks corresponding to PCL, nHA, and Ser, validating their successful integration and interaction within the scaffold matrix. Conclusions The nanofibrous scaffold exhibited structural and compositional properties, confirming the presence of PCL, nHA and Ser. The properties analyzed support its potential for biomineralization and tissue regeneration. The inclusion of Ser could enhance hydroxyapatite nucleation and cell attachment, making the scaffold a promising biomaterial for dentin repair. Further in-vitro and in-vivo studies are recommended to validate its clinical application.